The research process of clubroot disease and related control strategies in Brassica - Yaqi Deng; Zhiwen Zhang; Lili Liu; Tonghua Wang; Mei Li; Dawei Zhang; Mingli Yan (Oil Crop Science)
Brassica clubroot caused by Plasmodiophora brassicae has been identified as a severe soil-borne disease that poses a significant threat to plants root systems. The disease results in the formation of tumorous enlargements in the roots, leading to wilting and eventual plant death. Consequently, crop yield is drastically reduced, causing substantial economic losses in agriculture. The current study aims to provide a comprehensive overview of recent research process on Brassica clubroot, focusing on the biological characteristics, physiological race identification, and pathogenic mechanism of P. brassicae. Furthermore, it covers the latest advancements in the comprehensive prevention and clubroot control. The insights gained from this study are expected to contribute to the future research on clubroot and the development of resistance breeding strategies.